DESIGN OF CONTAINER TERMINAL LAYOUT IN PATIMBAN PORT USING GREEN PORT CONCEPT - Putri Prakoso (15514046), Hartiti
Patimban Port is one of many ports that under construction by Indonesian Government which located at Desa Patimban, Kabupaten Subang, West Java. There are four stages of Patimban Port construction project which named as Stage 1 Phase 1, Stage 1 Phase 2, Stage 2, and Stage 3. For this Final Project we will discuss about layout design and container terminal operation system of Patimban Port using Green port concept. Terminal layout can be designed by calculating the capacity of the terminal corresponding to the predicted containers flow, then we can design several alternatives layout using different container handling equipment. In Green port concept, one of solution to decrease production of emission is by using eco- friendly equipment, which we will analyze from several different equipment to get the best design. In the process before we eliminate the unwanted alternative, we should do emission analysis due to different power resource/ fuel and also financial analysis. If the equipment in accordance with term of the analysis then it can be chosen. From the emission analysis, power resource using electricity, gasoline, and propane have lower emission than using diesel, but from financial analysis an equipment using diesel has higher profit caused by cheapest price among others. Through other consideration, if thereÃ‚Â’s one equipment combination already fulfill both analysis above, then we can choose the best terminal layout of Patimban Port.